Primary adrenal insufficiency due to adrenal tuberculosis: a case report - Jie Yu; Yingli Lu; Bing Han (Journal of International Medical Research, 2020)
We report a case of primary adrenal insufficiency (PAI) due to adrenal tuberculosis with no findings of active tuberculosis in the lung of a 51-year-old female patient. The patient was admitted with a 10-year history of skin hyperpigmentation and was diagnosed with PAI. The primary cause was adrenal tuberculosis. An adrenocorticotropic hormone stimulation test, T-Spot test and adrenal computed tomography scan were used to confirm the diagnosis. The patient’s status improved, and the hyperpigmentation subsided after 15 months of treatment with anti-tuberculosis drugs and cortisol replacement therapy.